Choreographic thought: with a text you can also dance - Rodriguez, Maria Dolores Sosin (ODEERE, 2023)
The movement, transcribed here as choreography, serves as a methodology for reflecting on the role of the body in the production of knowledge in a broad sense: theoretical-artistic-scientific. Taking into consideration the relations between dance, word and literature, as well as the relations with other arts, various considerations are made, based on critiques of literature and culture, looking for interpretations for a black choreographic thought.